В сто первом зеркале: литературная критика / В. Я. Виленкин - Виленкин Виталий Яковлевич (Советский писатель, 1990)
Экземпляры: РБ (20191203☮) / Инвентарный номер: 23318 / Цена: 01.30 / Сис.шифр: 83.3(2Рос=Рус)6 / Авт.знак: В 44 / ББК: 83.3(2Рос=Рус)6